2019
DOI: 10.3390/nano9111539
|View full text |Cite
|
Sign up to set email alerts
|

Ce-Doped Graphitic Carbon Nitride Derived from Metal Organic Frameworks as a Visible Light-Responsive Photocatalyst for H2 Production

Abstract: Novel fibrous graphitic carbon nitride (g-C3N4) derivatives prepared from metal organic frameworks (MOFs) were doped with Ce3+ (Ce-C3N4) as photocatalytic materials. Ce-C3N4 was characterized using various techniques, revealing its high specific surface area, excellent photocatalytic activity, and stability for H2 evolution under visible light irradiation. The fluorine modified samples show superior photocatalytic activity under visible light irradiation, which is due to the presence of more active sites and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…[ 169 ] Lastly, the carbon and nitrogen sources in MOFs can be used as precursors to form highly photoactive materials such as g‐C 3 N 4 . [ 170 ] All of the above results demonstrate that MOFs are unique precursors for hybrid photocatalysts with porous structures for effective mass transport and rapid charge transport to suppress charge recombination.…”
Section: Why Mof Hybrids?mentioning
confidence: 94%
“…[ 169 ] Lastly, the carbon and nitrogen sources in MOFs can be used as precursors to form highly photoactive materials such as g‐C 3 N 4 . [ 170 ] All of the above results demonstrate that MOFs are unique precursors for hybrid photocatalysts with porous structures for effective mass transport and rapid charge transport to suppress charge recombination.…”
Section: Why Mof Hybrids?mentioning
confidence: 94%
“…The researchers further modified the sample with NH 4 F to make the fiber morphology of the sample finer and the dispersion better, which further improved the active site and enhanced the absorption of solar energy. 133…”
Section: Photocatalysismentioning
confidence: 99%
“…In addition, various existing researches have proven that implanting the anion–cation into the g-C 3 N 4 frameworks could regulate their bandgap structure for broader visible-light absorption, facilitate the bulk phase and interface charge separation and lead to enhanced photocatalytic activity for H 2 evolution [ 21 , 22 , 23 ]. For instance, Qiao et al [ 24 ] found that a new intermediate energy level was formed in the bandgap of g-C 3 N 4 via the insertion of P into its skeleton, which received the electrons generated by light excitation from VB and thus improved the separation of photocarriers.…”
Section: Introductionmentioning
confidence: 99%